Again modernization? The missing link in development - Castillo Ochoa, Manuel (2018)
This essay explores the vicissitudes and dilemmas that lies behind the promise of modernization that the current government of Peru has been doing. To do so, based on what the current government identifies as “let’s do it!” to reach modernization, goes over, from Latin American’s sociologic critical theory, the debates of development. Reviews the proposals of the theory of dependency and power Decoloniality and finds what could be one of the proposals to maximize development, since non critical social thought. Latin American social theory approaches are analyzed from the modernization, dependency, decoloniality, to the proposal of the dependent industrialization and its recent reformulations.